Variations in Element Levels Accumulated in Different Parts of Boletus edulis Collected from Central Yunnan Province, China - Xue-Mei Wang; Ji Zhang; Tao Li; Jie-Qing Li; Yuan-Zhong Wang; Hong-Gao Liu (Journal of Chemistry)
ICP-AES and microwave assisted digestion were applied to determine P, Mg, Ca, Zn, Na, Cu, Ba, Ni, V, Cd, Sr, Co, and Li in the caps and stipes of Boletus edulis collected from six spatially distant sites in Yunnan province, China. Fruiting bodies of King Bolete are abundant in P, Mg, Ca, Zn, Cu, and Na, followed by Ba, Cd, Ni, V, Li, Sr, and Co. Contents of P, Mg, Zn, and Cu are more abundant in caps than in stipes of King Bolete. However, elements such as Na, Ba, Cd, Ni, V, Li, Sr, and Co prefer to accumulate in stipes of mushrooms from Yaoan, Chuxiong. The results of this study indicate that spatial variations of elements between caps and stipes are mainly related to different bedrock soil geochemistry and enrichment capability for various elements.